The flexural strength of polystyrene sandwich beam - Nur Hazwani, Alias (2013)
During construction, the formwork for beam is widely used. This contributes to the increase in cost and time for the project. A precast beam is an alternative solution to do away with the formwork. One such beam which is gaining around is the polystyrene sandwich beam. A sandwich beam is a special form of laminated composite fabricated by attaching two thin but stiff skins to the lightweight but thick core. The benefits of using the sandwich concept in structural components are its high bending and high strength to weight ratios. This research aims to investigate the flexural strength of the polystyrene sandwich beam and also the crack pattern of the beam. It is achieved by using the Four Point Flexural Bending Test, (FPB). There are three types of sample. For sample 1 and 2, the beam consists of polystyrene wrapped with wire mesh and covered with concrete. Sample 3 is the same with sample 1 and 2 but has the reinforcement bars at the bottom of the beam. The highest load for this research is 21 .6kN of sample 3 and the value for the its flexural strength is 15 kPa. The shear crack pattern can only be obtained from the sample 3 but none from sample 1 and 2. This research has produced a new sandwich beam design using polystyrene, which is also a form of precast beam under the Industrial Building Service (IBS).